Faktor-Faktor yang Mempengaruhi Penyerapan Tenaga Kerja Pada Sektor Pertanian di Sumatera Utara - Hardai Hasibuan, Andika Pramana; Ginting, Rahmanta; Effendi, Ihsan (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2019)
This study aims to determine what factors influence labor absorption in agriculture sector. The research method used is descriptive analysis with a quantitative approach using multiple regression equations using series 7 Eviews software. This research used time series data from 1986 until 2016. This research using labor absorption as dependent variable and the independent variables are inflation, investation, and provincial minimum wage. The results of the study show that inflation and investment variables have a significant positive effect on employment. The provincial minimum wage has a negative effect on employment in the agricultural sector in North Sumatra Province.